UNIVERSAL PATTERNS, LOCAL VOICES: A STRUCTURAL ANALYSIS OF NARRATIVE AND CHARACTER ARCHETYPES IN BALTI FOLKTALES - Miss Nazia Ashraf; Maryam Fatima; Muhammad Naseem (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores three Balti folktales through the lens of structuralism, focusing on narrative patterns and character archetypes as articulated by Vladimir Propp's Morphology of folktales. Folktales, traditionally transmitted orally across generations in Baltistan, serve as cultural artifacts reflecting universal storytelling mechanisms and societal values. The analysis, drawn from Vanishing Words of Wisdom, originally recorded in Balti and translated into English, applies Propp's framework to uncover underlying narrative structures. While enriching literary and anthropological discourse on narrative theory and cultural transmission, the study acknowledges limitations in generalizing findings beyond this specific cultural context and nuances lost in translation. This research contributes to understanding how folktales transcend mere stories to embody complex cultural narratives.